Strategi Pengelolaan Koin NU di LAZIS NU Kabupaten Blitar untuk Menyejahterakan Masyarakat Perspektif Maqashid Syari’ah - Nisa, Zulia Khoirun; Abdillah, Bacharuddin; Adin, Muhammad Faaza (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
NU Care has populist programs. The aim of these programs is to bridge the gap between the alms giver and the recipient. NU Care, through the NU coin, provides a way for ordinary people so they don't mind when they have to give alms, so they can still give alms even in small amounts. This study aims to analyze the management of NU coin infaq funds for the welfare of the community; as well as analyzing the management of NU coin infaq funds for the welfare of society from the maqashid sharia perspective. The method used is a descriptive qualitative approach by taking samples in several villages in the Blitar Regency and the Amil Zakat and Sedekah NU Institution offices in Blitar Regency. The management of NU coin funds carried out by the Amil Zakat and Sedekah Nahdlatul Ulama Institute in Blitar Regency for the welfare of the community is as follows: fundraising, distribution, utilization, 2) while from the perspective of maqashid syari'ah, what has been done by the Amil Zakat and Sedekah Institution Nahdlatul Ulama Blitar Regency is in accordance with the concept of maqashid syari'ah where there is an element of benefit from the program being implemented. Besides that, there is also the concept of welfare which is also appropriate.